2018
DOI: 10.18677/encibio_2018a34
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico Da Morbidade E Mortalidade Dos Casos De Leptospirose No Nordeste Brasileiro Entre 2000 a 2015

Abstract: The objective of the study was to perform a diagnosis of the morbidity and mortality of Leptospirosis cases in the Brazilian Northeast (NEB). The time series of leptospirosis from 2000 to 2015 was obtained from DATASUS, being evaluated through descriptive and exploratory statistics. The results obtained from the descriptive statistics applied to the time series showed that the years (2000, 2004,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
(17 reference statements)
0
4
0
4
Order By: Relevance
“…Organization for Animal Health (OIE) as the world's most widespread zoonosis (BRASIL, 2008). In the Brazilian Northeast, between 2000 and 2015, Pernambuco was the state with the highest morbidity (41.10%) and mortality (10.83%) of humans due to leptospirosis (SANTOS et al, 2018). In Brazil, leptospirosis is a reportable disease under epidemiological surveillance in both humans and animals.…”
Section: Leptospirosis Is Recognized By the Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…Organization for Animal Health (OIE) as the world's most widespread zoonosis (BRASIL, 2008). In the Brazilian Northeast, between 2000 and 2015, Pernambuco was the state with the highest morbidity (41.10%) and mortality (10.83%) of humans due to leptospirosis (SANTOS et al, 2018). In Brazil, leptospirosis is a reportable disease under epidemiological surveillance in both humans and animals.…”
Section: Leptospirosis Is Recognized By the Worldmentioning
confidence: 99%
“…Classified as a bacterial anthropozoonosis that affects domestic, wild, and synanthropic animals, leptospirosis is caused by pathogenic species of the genus Leptospira (BATISTA et al, 2016), with many serogroups identified, each of them having its preferred hosts (SANTOS et al, 2018). Some authors, such as Pinna et al (2008), consider equids as the main reservoirs for the Australis serogroup.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies based on future climate projections have shown a significant increase in temperature and a drastic reduction in rainfall, followed by prolonged periods of drought and severe droughts and, finally, a trend towards aridity in the region causing desertification (Marengo et al 2017). The northeastern population is vulnerable to these climatic extremes, which often cause deaths, environmental damage, and socioeconomic impacts, and still affect the population with water‐borne diseases, after their occurrences (Monteiro, 1976; Cairncross and Feachem, 2018; Santos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These are further classified by serology into more than 300 different serovars of which more 250 are known to infect humans (2). Leptospirosis is strongly associated with environmental factors including heavy rainfall, flooding, population growth, poor sanitation and hygiene and disasters (3,4).…”
Section: Introductionmentioning
confidence: 99%